The age-related changes and sex difference in master swimming performance - Knechtle, Beat (2020)
Master athletes have been widely used to examine the age-induced decline of human performance. However, so far very limited reviews are available consolidating the age-related differences in master swimming performance. The aim of the present review was to summarize existing knowledge about the age-related changes in three modalities of swimming performance (i.e., pool-swimming, open-water swimming and swim split in triathlons of different distances). In addition, the paradigm of freestyle swimming records from 50 to 1500mwas used to examine age-related differences and sex difference in performance for age groups 25–29 to 100–104 years. For this example of master freestyle swimmers, the sex difference was smaller in the longer events and increased significantly after the age of ∼70 years. In summary, master athletes competing in swimming as single discipline (i.e., pool-swimming and open-water) and in triathlon (i.e., swim split as first discipline) improved their performances across calendar years. The age-related performance decline in swimming seems to be specific to the discipline, the sex and the length of the swimming event.